Perfil microbiológico de ovos sem inspeção veterinária adquiridos em comércio informal do Rio Grande do Sul, Brasil - Didoné, Simone Rosa (2017)
The per capita eggs consumption in Brazil is increasing at a rate of 148 eggs per person per year in 2010, while in 2015 it have already been reched 191 eggs per person / year. Not only consumption is increasing, but the consumer demand has also increased for eggs produced in less intensive systems, as in the case of backyard eggs. However, in the quest to consume eggs from backyard production systems, some people end up purchasing products without veterinary inspection in the informal trade or even raising the laying hens in their own home. Among foods responsible for food poisoning, eggs are incriminated as major sources of bacterial agents. The objective of this study was to evaluate the microbiological quality of eggs in the informal commerce of Rio Grande do Sul. Samples of 480 eggs (separated in clear, yolk and peel) were processed according to Instrução Normativa Nº. 62 / 2003 and Portaria nº 01/1990, of the Ministério da Agricultura, Pecuária e Abastecimento. All samples reached the recommended level in the law when evaluated the count of aerobic mesophiles, but did not obtain satisfactory results for the requirements regarding the presence of Staphylococcus spp. and total coliforms. In addition to the bacterial count, several enterobacteria were also diagnosed in raw eggs, with Escherichia coli, Citrobacter freundii, Enterobacter cloacae, Enterobacter aerogenes, Cedecea sp. and Edwardsiella ictaluri. The external contamination of the egg had significant positive statistical correlation with the bacterial contamination of the white and yolk. Therefore, it was concluded that the eggs sampled showed unsatisfactory results for almost all the quantitative evaluations, being within the norms required only with respect to aerobic mesophiles. Bacteria potentially causing foodborne diseases were evidenced, with special attention to Escherichia coli as the most present in the samples in most cities evaluated. The genus Salmonella spp. was not found in any sample. The presence in high number of Staphylococcus spp. In the clear and yolk demonstrates the need to expand the investigation of this pathogen in food, as there are strong indications of underdiagnosis in both food poisoning and food for human consumption.